Evaluation of Promoter Methylation of RASSF1A and ATM in Peripheral Blood of Breast Cancer Patients and Healthy Control Individuals - Cao, Xue; Tang, Qiuqiong; Cuk, Katarina; Schott, Sarah; Heil, Jörg; Golatta, Michael; Sohn, Christof; Schneeweiss, Andreas; Burwinkel, Barbara (International journal of molecular sciences, 2018)
Breast cancer (BC) is the most common cancer among women and has high mortality rates. Early detection is supposed to be critical for the patient’s prognosis. In recent years, several studies have investigated global DNA methylation profiles and gene-specific DNA methylation in blood-based DNA to develop putative screening markers for cancer. However, most of the studies have not yet been validated. In our study, we analyzed the promoter methylation of RASSF1A and ATM in peripheral blood DNA of 229 sporadic patients and 151 healthy controls by the MassARRAY EpiTYPER assay. There were no significant differences in DNA methylation levels of RASSF1A and ATM between the sporadic BC cases and the healthy controls. Furthermore, we performed the Infinium HumanMethylation450 BeadChip (450K) array analysis using 48 sporadic BC cases and 48 healthy controls (cases and controls are the same from those of the MassARRAY EpiTYPER assay) and made a comparison with the published data. No significant differences were presented in DNA methylation levels of RASSF1A and ATM between the sporadic BC cases and the healthy controls. So far, the evidence for powerful blood-based methylation markers is still limited and the identified markers need to be further validated.
Gesehen am 27.03.2019